Decentralisation and supply efficiency of RWS in India - Anand N. Asthana (2003)
This paper looks at supply of safe drinking water in India. In India the state and the local governments are responsible for providing safe drinking water. International aid in the field of drinking water is a very small proportion of total investment and so policy in this sector has largely been autonomous.